Amphotericin-B in the Management of Resistant Kala-azar - Islam, Quazi Tarikul; Ekram, ARM Saifuddin; Aziz, Ahmad Monjural; Refazuddin, Md; Rahman, Md Mahbubur; Alim, MA; Flora, Ms; Hakim, Md (TAJ: Journal of Teachers Association, 2009)
Kala-azar is a re-emerging global problem. Recent years have shown a notable improvement in both morbidity and mortality in patients with Kala-azar. Much of this benefit is derived from the use of the newer therapeutic agents. Among these Amphotericin-B deoxycholate for the treatment of resistant Kala-azar is very effective and offer many advantages. We report a case of resistant Kala-azar where we used Amphotericin-B deoxycholate and it showed a very good clinical and parasitological response. doi: 10.3329/taj.v17i2.3459 TAJ 2004; 17(2): 110-112